Fault Control Method of New Energy Through Flexible DC System Based on Coordination of Stability Control and Energy Dissipation Device - Chen, Kuiye; Gu, Yican; Zhang, Xingzi; Lu, Qiyun (2024 5th International Symposium on New Energy and Electrical Technology (ISNEET), 2024)
Due to the difficulty in matching the development speed of voltage and current after the failure of the DC power grid and the time to cut off the new energy unit through the AC safety control device, any disturbance may cause the surplus power of the DC power grid, which will lead to a large-scale paralysis of the DC power grid. To solve this problem, this paper takes a DC network as an example to analyze the surplus power of DC network and analyzes the adaptability of energy-consuming devices to consume surplus power. On this basis, a new DC energy-consuming topology is designed, and its parameters are designed, and the switching strategy of energy-consuming devices is put forward. Finally, the coordinated control strategy between the energy-consuming device and the stable control system is proposed. The simulation results show that this method can effectively improve the fault ride-through ability of the new energy to send out the system fault through flexibility.